2019
DOI: 10.1089/ars.2017.7424
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxalase 1 Modulation in Obesity and Diabetes

Abstract: Glo1 inducers may now be evaluated in Phase 2 clinical trials for treatment of NAFLD and vascular complications of diabetes. Antioxid. Redox Signal. 00, 000-000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 200 publications
2
76
0
3
Order By: Relevance
“…However, there is need to devise novel approaches to lower AGEs by harnessing the endogenous defenses in place, which are likely to prevent AGE formation and potentially pose fewer side effects. In a recent promising clinical trial, a combination therapy of trans-Resveratrol (tRes) and Hesperetin (HESP) helped improve glycemic control and vascular inflammation in healthy overweight and obese individuals via induction of Glo1 (Rabbani and Thornalley, 2018b). This suggests that inhibition of MGO accumulation via induction of glyoxalases could be a potential therapeutic strategy for glycation-mediated diseases.…”
Section: Glyoxalases As a Target For Therapymentioning
confidence: 99%
“…However, there is need to devise novel approaches to lower AGEs by harnessing the endogenous defenses in place, which are likely to prevent AGE formation and potentially pose fewer side effects. In a recent promising clinical trial, a combination therapy of trans-Resveratrol (tRes) and Hesperetin (HESP) helped improve glycemic control and vascular inflammation in healthy overweight and obese individuals via induction of Glo1 (Rabbani and Thornalley, 2018b). This suggests that inhibition of MGO accumulation via induction of glyoxalases could be a potential therapeutic strategy for glycation-mediated diseases.…”
Section: Glyoxalases As a Target For Therapymentioning
confidence: 99%
“…Dicarbonyl metabolites can also contribute to the progression and development of diabetic kidney diseases. The tRES‐HESP formulation of resveratrol may therefore deliver glyoxalase‐1–mediated beneficial effects in such cases . Apart from the combination approach, administration of resveratrol, also showed significant impact on reducing the blood glucose level in overweight subjects …”
Section: Completed Clinical Trialsmentioning
confidence: 99%
“…90 It has been demonstrated that increased glyoxalase 1 expression slows down the progression of obesity and insulin resistance by alleviating dicarbonyl metabolites such as methylglyoxal. 91 A coformulation of trans-resveratrol and hesperetin (tRES-HESP) significantly increased the expression of glyoxalase 1 and decreased the plasma methylglyoxal and total body methylglyoxal-protein glycation in overweight subjects. 92 The coformulation also significantly decreased fasting and postprandial plasma glucose levels, and improved insulin sensitivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MG is detoxified by enzymes glyoxalase 1 and 2 (Glo1, Glo2) to D-lactate (in contrast to Llactate, the end product of glycolysis), which can be measured in peripheral blood, and serves as a surrogate marker of whole-body MG production (19). Previously, we demonstrated that nine days of an isocaloric fructose-restricted diet reduced available substrate for DNL and resultant liver fat in children with obesity and metabolic syndrome who identified as high habitual sugar consumers (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%